Biodisponibilidade como parâmetro de qualidade e sua importância no registro de medicamentos - Amorim, Roberta Meneses Marquez de (2004)
This work will discuss the bioavailability of drug, how it is changed and its importance as a quality pattern to the registration of medicines in Brazil. In this light, bioavailability will be previously conceptualized and discussed together with other topics relevant to the comprehension of this work. Bioavailability can be affected by both the patient conditions and the drug itself. In what regards the patient conditions, the important factors discussed here are gastrointestinal treatment, place of absorption, genetics factors, body weight, age, gender and physiological changes caused by illness. With regard to the drug, topics such as physical state, polymorphism, size of particle, state of solvability, characteristics of ionization, coefficient of partition, chemical alterations, complex formation, stereochemistry activity, inactivation before absorption, link to plasmatic and tissue proteins and selectivity in the place of absorption. Among the same lines, the formulation of medicines are also discussed, specially issues such as pharmaceutics’ form, the size of particles, superficial area, type and quantity of excipients, variables of the manufacture process and the speed of dissolution of medicines. It is also presented a proposal of a protocol of study of bioavailability covering topics like dosing, outline of the study, the subject of the research, previous studies, analytical methodology, pharmacokinetic and statistics analysis. In the realm of regulation, considering the influence of biopharmacotecnic and physiological factors in the bioavailability of medicines, this work argues for the importance of previous submission of biodisponibility studies as a condition for the registration of medicines.